Automated road marking recognition system - Ziyatdinov, R R; Shigabiev, R R; Talipov, D N (IOP conference series. Materials Science and Engineering, 2017)
Development of the automated road marking recognition systems in existing and future vehicles control systems is an urgent task. One way to implement such systems is the use of neural networks. To test the possibility of using neural network software has been developed with the use of a single-layer perceptron. The resulting system based on neural network has successfully coped with the task both when driving in the daytime and at night.